Supplementation of dairy cows with bovine somatotropin or omega-3 rich fish oil affects the endometrial expression of peroxisome proliferator-activated receptors - Leslie A. MacLaren; Todd R. Bilby; Frank Michel; Aydin Guzeloglu; Charles R. Staples; William W. Thatcher (Eurasian Journal of Veterinary Sciences)
Aim: The study objectives were to determine whether dietary supplementation with long chain omega-3 polyunsaturated fatty acids in the form of enriched fish oil (FO) for 90 days or treatment with bovine somatotropin (bST) at the time of ovulation and 11 days post-ovulation influenced PPAR expression and activation in bovine endometrium in Holstein cows. Materials and Methods: Non-lactating cows were assigned to one of four treatments: cyclic, cyclic-bST, pregnant or pregnant-bST. Lactating cows were assigned to one of six treatments: cyclic, cyclic-bST, pregnant, pregnant-bST, cyclic-FO or cyclic-FO-bST. Results: Northern and Western blot analyses indicated that PPARα and PPARδ, but not PPARγ, are expressed in endometrium from all cows at day 17 post-ovulation. Treatment with bST is associated with increased PPARδ mRNA abundance in pregnant but not cyclic cows, suggesting that the effect may be mediated by the embryo. Increased abundances of PPARα mRNA are observed in response to bST during pregnancy in lactating cows but not in non-lactating cows, highlighting the importance of lactation status in determining bST response. Fish oil supplementation is associated with reduced PPARδ mRNA abundance, but did not affect steady-state PPARα mRNA abundance. PPARδ protein is expressed in the luminal epithelium, glandular epithelium, subepithelial stroma and to a lesser extent in the adluminal stroma. Anti-PPARδ reactivity is reduced in response to bST and fish oil treatments in pregnant cows. Conclusion: bST and fish oil treatments affect endometrial PPARα and PPARδ expression in lactating dairy cows.